Evaluation of the P13K pathway and downstream effect in Her-2 positive and negative breast carcinomas - Rademan, Anina (Division of Anatomical Pathology, 2015)
Breast cancer management continues to be a challenge due to the heterogeneity of the disease and the fact that individuals with the same stage and pathological diagnosis may respond differently to treatment as a result of differences in gene expression. Several components of the Her-2/PI3K/Akt pathway were evaluated for their relevance as potential prognostic markers or indicators for treatment. A secondary objective was to evaluate the CISH technique for its suitability for analysis of Her-2 gene amplification on archived, Papanicolaou-stained fine needle aspiration (FNA) samples. Tissue blocks from a retrospective series of 93 primary breast carcinoma cases were selected, based on their Her-2 status. Twenty six of these cases received trastuzumab treatment while 67 did not. Expression of Her-2, ER, PI3K, PTEN, p-Akt, BCL2, NFÎºB, MDM2 and p53 were analysed and compared with various clinicopathological features. The CISH technique was evaluated for its suitability for analysis of Her-2 gene amplification on archived, Papanicolaou-stained FNA samples.